2020
DOI: 10.1038/s41551-020-00603-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a Cas13-based assay for the detection of SARS-CoV-2 RNA

Abstract: Nucleic-acid detection via isothermal amplification and collateral cleavage of reporter molecules by CRISPR-associated enzymes is a promising alternative to quantitative polymerase chain reaction (qPCR). Here, we report the clinical validation of the SHERLOCK (specific high-sensitivity enzymatic reporter unlocking) assay using the enzyme Cas13a from Leptotrichia wadei for the detection of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) -the virus that causes COVID-19 (coronavirus disease 2019) -in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
515
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 518 publications
(566 citation statements)
references
References 32 publications
25
515
5
1
Order By: Relevance
“…If multiple studies were conducted on the same set of patient samples, only a study with the highest sensitivity and specificity was used. For example, Patchsung et al 67 reported two CRISPR diagnosis studies on the same set of patient samples, one using fluorescent readout and the other using lateral flow assay. In our analysis, we included only the fluorescent readout study, which had higher sensitivity and similar specificity to the lateral flow assay.…”
Section: Publication Bias Publication Bias Of All 81 Included Studiementioning
confidence: 99%
“…If multiple studies were conducted on the same set of patient samples, only a study with the highest sensitivity and specificity was used. For example, Patchsung et al 67 reported two CRISPR diagnosis studies on the same set of patient samples, one using fluorescent readout and the other using lateral flow assay. In our analysis, we included only the fluorescent readout study, which had higher sensitivity and similar specificity to the lateral flow assay.…”
Section: Publication Bias Publication Bias Of All 81 Included Studiementioning
confidence: 99%
“…Notably, target genes in buccal samples can be detected electrically via inactivated Cas9 immobilized on a graphene field-effect transistor without the need for amplification 2 , and Cas13 has been used to monitor opportunistic viral infections in blood and urine samples following organ transplantation, and to detect transplant rejection in urine samples 3 . And, most recently, fast and inexpensive lateral-flow fluorescence assays containing Cas12a or Cas13a can detect SARS-CoV-2 RNA accurately in nasopharyngeal samples [4][5][6] .…”
mentioning
confidence: 99%
“…Comparison with RT-PCR results showed that both were in complete agreement. 70 A simple and rapid assay called the “all in one dual CRISPR-Cas12a” has recently been developed for the detection of SARS-CoV-2 with high sensitivity and high detection specificity. It can be carried out as a single tube reaction and provides visual detection for which it could be used as a point-of-care test.…”
Section: Nanoarchitectronics In Diagnosis and Detection Of Covid-19mentioning
confidence: 99%